Study on Hydraulic Characteristics of Reactor Coolant Pump Shutdown Transition Process Based on Primary Circuit Closed System - Li, Dong-hao; Li, Yi-bin; Zhang, Fan; Guo, Yan-lei; Yang, Cong-xin; Wang, Xiu-yong (Frontiers in Energy Research, 2022)
According to the structural characteristics of a steam generator and a reactor pressure vessel, the reactor primary circuit system of HPR1000 is simplified to make the reactor coolant pump (RCP) characteristics match the resistance characteristics of the system pipeline, so a simplified model of reactor primary circuit closed system is formed. On this basis, the RCP shutdown accident in a single circuit of the reactor is numerically simulated. Results show that the pressure in the pipeline system has changed greatly compared. The flow rate drops rapidly and decreases to 1.7% of stable operation at 10s. The torque drops sharply to −51.89% of stable operation, and then rises slowly to zero. The pressure at the inlet and outlet of the impeller changes dramatically which leads to the change of blade load and the velocity in the impeller passage decreases gradually. The pressure and velocity in the guide vane continue to decrease.